2018
DOI: 10.1002/htj.21403
|View full text |Cite
|
Sign up to set email alerts
|

MHD boundary layer bionanoconvective non‐Newtonian flow past a needle with Stefan blowing

Abstract: The purpose of the article is to present a transport model for magnetohydrodynamics‐forced convective non‐Newtonian boundary flow from a thin needle in a nanofluid in the presence of microorganisms and Stefan blowing. The governing equations are reduced to ordinary differential equations with the help of similarity transformations and then numerically solved by using the Matlab bvp4c function. The effect of various emerging parameters on the flow field, heat, mass, and density of motile microorganisms transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 35 publications
(65 reference statements)
0
23
0
Order By: Relevance
“…The reader can further study about the bioconvection fluid flow with different geometries and flow conditions in Refs. 33 – 37 .…”
Section: Introductionmentioning
confidence: 99%
“…The reader can further study about the bioconvection fluid flow with different geometries and flow conditions in Refs. 33 – 37 .…”
Section: Introductionmentioning
confidence: 99%
“…The bio-convective patterns around a truncated cone were also observed by Khan and co-researchers 27 and elucidated bioconvection flow of nano-material over truncated cone. The investigation for bioconvection flow of nanofluid in presence of Stefan blowing features has been suggested by Amirsom et al 28 . Dero et al 29 evaluated the slip effects and Stefan blowing effects in flow of nanofluid configured by shrinking surface.…”
mentioning
confidence: 99%
“…Chebyshev method has used in this investigation for approximate solution of problem. The reader can further study about the bioconvection fluid flow with different geometries and flow conditions in Refs [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…From above cited literature, we observe that many investigations have conducted for fluid flow upon a thin needle by using various flow conditions, but only one study [40] has found in literature that discussed the fluid flow with motile microorganism upon a thin moving needle. In this work [40] traditional nanofluid has used. In our work we have considered the thermal analysis for bioconvection of hybrid nanofluid flowing upon a thin horizontally moving needle.…”
Section: Introductionmentioning
confidence: 99%